Aplicação da metodologia de planejamento de experimentos para formulação de massas cerâmicas para telhas - Macedo, Rose Meire Penha Revoredo de (2007)
Rio Grande do Norte State stands out as one great producer of structural clay of the brazilian northeastern. The Valley Assu ceramic tiles production stands out obtained from ilitics ball clays that abound in the region under study. Ceramics formulation and the design of experiments with mixture approach, has been applied for researchers, come as an important aid to decrease the number of experiments necessary to the optimization. In this context, the objective of this work is to evaluate the effects of the formulation, temperature and heating rate in the physical-mechanical properties of the red ceramic body used for roofing tile fabrication of the Valley Assu, using design of mixture experiments. Four clays samples used in two ceramics industry of the region were use as raw material and characterized by X-ray diffraction, chemical composition, differential thermal analysis (DTA), thermogravimetric analysis (TGA), particle size distribution analysis and plasticity techniques. Afterwards, they were defined initial molded bodies and made specimens were then prepared by uniaxial pressing at 25 MPa before firing at 850, 950 and 1050 ºC in a laboratory furnace, with heating rate in the proportions of 5, 10 e 15 ºC/min. The following tecnologicals properties were evaluated: linear firing shrinkage, water absorption and flexural strength. Results show that the temperature 1050 ºC and heating rate of 5 ºC/min was the best condition, therefore presented significance in all physical-mechanical properties. The model was accepted as valid based of the production of three new formulations with fractions mass diferents of the initial molded bodies and heated with temperature at 1050 ºC and heating rate of 5 ºC/min. Considering the formulation, temperature and heating rate as variables of the equations, another model was suggested, where from the aplication of design of experiments with mixtures was possible to get a best formulation, whose experimental error is the minor in relation to the too much formulations